Models for Gut-Mediated Horizontal Gene Transfer by Bacterial Plasmid Conjugation - Ott, Logan C.; Mellata, Melha (Frontiers in Microbiology, 2022)
Emergence of new bacterial strains may pose a threat to human and animal health. Bacterial conjugation is a significant contributor to rapid microbial evolutions that contributes the emergence and spread of antimicrobial resistance (AR). The gut of animals is believed to be a potent reservoir for the spread of AR and virulence genes through the horizontal exchange of mobile genetic elements such as plasmids. The study of the plasmid transfer process in the complex gut environment is limited due to the confounding factors that affect colonization, persistence, and conjugation. Furthermore, study of plasmid transfer in the gut of humans is limited to observational studies, leading to the need to identify alternate models that provide insight into the factors regulating conjugation in the gut. This review discusses key studies on the current models for in silico, in vitro, and in vivo modeling of bacterial conjugation, and their ability to reflect the gut of animals. We particularly emphasize the use of computational and in vitro models that may approximate aspects of the gut, as well as animal models that represent in vivo conditions to a greater extent. Direction on future research studies in the field are provided.